Heparin-Binding Protein: A Prognostic Biomarker Associated with Severe or Complicated Community-Acquired Pneumonia in Children - Li S; Xu Y; Wu Y; Huang H; Sun C; Xu S; Li H; Zhang X; Zhao S; Huang L (Dove Medical Press, 2023)
Shuang Li,1,2,* Yanwen Xu,2,* Yuhang Wu,2,* Heyu Huang,2 Chen Sun,2 Shanshan Xu,2 Huajun Li,2 Xi Zhang,3 Shiyong Zhao,4 Lisu Huang1,2 1Department of Infectious Diseases, The Children's Hospital, Zhejiang University School of Medicine, National Clinical Research Center for Child Health, Hangzhou, Zhejiang, People's Republic of China; 2Department of Infectious Diseases, Xinhua Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, People's Republic of China; 3Clinical Research Unit, Xinhua Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, People's Republic of China; 4Department of Infectious Diseases, Hangzhou Children's Hospital, Hangzhou, Zhejiang, People's Republic of China*These authors contributed equally to this workCorrespondence: Lisu Huang, Department of Infectious Diseases, The Children's Hospital, Zhejiang University School of Medicine, National Clinical Research Center for Child Health, 3333 Binsheng Road, Hangzhou, Zhejiang Province, 310052, People's Republic of China, Email lisuhuang@zju.edu.cn Shiyong Zhao, Department of Infectious Diseases, Hangzhou Children's Hospital, 195 Wenhui Road, Hangzhou, Zhejiang Provinve, 310005, People's Republic of China, Email jhzsyhj@163.comPurpose: Heparin-binding protein (HBP) is a novel biomarker for inflammatory diseases. This study aimed to investigate the role of serum HBP in community-acquired pneumonia (CAP) in children and the association of HBP with the severity and prognosis.Patients and Methods: A total of 125 children with CAP admitted to the hospital were enrolled in this retrospective study. We analyzed the differences in clinical characteristics and examination findings between patients with different levels of HBP. The severe or complicated CAP was defined as having severe radiographic findings and/or systemic manifestations. Receiver operator characteristic (ROC) curves detected the performance of biomarkers in identifying patients with severe or complicated pneumonia. The multivariate logistic regression models assessed the association between HBP levels and the severity and prognosis. Finally, we constructed a predictive model based on HBP.Results: The rate of severe or complicated CAP for patients with upper-quartile HBP concentration (≥ 60 ng/mL) was 54.8%, significantly higher than that of patients with lower HBP concentration (26.6%). The level of HBP is substantially correlated with neutrophil counts, C-reactive protein, erythrocyte sedimentation rate, and serum amyloid A protein (r = 0.31, 0.26, 0.36, and 0.26, respectively). HBP achieved the highest level of discrimination for severe or complicated CAP among the biomarkers. Higher HBP concentration (≥ 60 ng/mL) was associated with a three-fold higher risk of severe or complicated CAP (adjusted odds ratio = 3.11, p < 0.05). A predictive model including four characteristics (HBP, lactate dehydrogenase, age and non-viral infection) for predicting severe or complicated CAP (with area under the ROC curve = 0.75) was built to create a nomogram.Conclusion: Substantially elevated serum HBP is significantly associated with severe or complicated CAP and poor prognosis in children. This finding warrants further investigation of the function of HBP in the pathogenesis of CAP.Keywords: pneumonia, biomarker, heparin-binding protein, children